Impact of surgically maximized versus native membranous urethral length on 30-day and long-term pad-free continence after robot-assisted radical prostatectomy - Ko, Young Hwii (Prostate Int, 2020)
BACKGROUND: Pelvic multiparametric magnetic resonance imaging (mpMRI)–determined membranous urethral length (MUL) and its surgical maximization have been reported to impact early- and long-term pad-free urinary continence after robot-assisted radical prostatectomy (RARP). OBJECTIVE: The objective of this study was to present evidence (data and video) of important effects on post-RARP continence recovery from both innate mpMRI-assessed and surgical preservation of MUL. DESIGN, SETTING AND PARTICIPANTS: Of 605 men undergoing RARP, 580 with complete follow-up were included: Group 1, prior (N = 355), and Group 2, subsequent (N = 225) to technique change of MUL maximization. Effect of innate, mpMRI-assessed MUL on postoperative continence was assessed. SURGICAL PROCEDURE: Before technique change, the dorsal venous complex was stapled before transection of the membranous urethra. After the change, the final step of extirpation was transection of the dorsal venous complex and periurethral attachments, thus facilitating surgical maximization of MUL. MEASUREMENTS: Primary and secondary outcomes for technique change and mpMRI-assessed MUL were both patient-reported 30-day and 1-year pad-free continence after RARP, respectively. RESULTS: Preoperative prostate-specific antigen, age, and disease aggressiveness were significantly higher in Group 2. After technique change and surgical maximization of MUL, 30-day and 1-year pad-free continence were both significantly improved (p < 0.05). In multivariate analysis, maximization of MUL significantly increased the likelihood of both early- and long-term continence recovery. For men undergoing MUL preservation, mpMRI-assessed MUL>1.4 cm also independently predicted higher 30-day (odds ratio: 4.85, 95% confidence interval: 1.24-18.9) and 1-year continence recovery (odds ratio: 11.26, 95% confidence interval: 1.07-118). CONCLUSIONS: Prostatic rotation and circumferential release of apical attachments and maximization of MUL improves continence after RARP. Separately, innate MUL>1.4 cm independently increased 30-day and 1-year continence recovery. PATIENT SUMMARY: Surgeon efforts to maximize MUL during radical prostatectomy are highly encouraged, as maximally preserved MUL likely improves post-RARP continence recovery. In addition, individual patients’ mpMRI-assessed MUL (approximately >1.4 cm) independently limits continence recovery.